miR-29b supplementation decreases expression of matrix proteins and improves alveolarization in mice exposed to maternal inflammation and neonatal hyperoxia - Durrani-Kolarik, Shaheen (Am J Physiol Lung Cell Mol Physiol, 2017)
Even with advances in the care of preterm infants, chronic lung disease or bronchopulmonary dysplasia (BPD) continues to be a significant pulmonary complication. Among those diagnosed with BPD, a subset of infants develop severe BPD with disproportionate pulmonary morbidities. In addition to decreased alveolarization, these infants develop obstructive and/or restrictive lung function due to increases in or dysregulation of extracellular matrix proteins. Analyses of plasma obtained from preterm infants during the first week of life indicate that circulating miR-29b is suppressed in infants that subsequently develop BPD and that decreased circulating miR-29b is inversely correlated with BPD severity. Our mouse model mimics the pathophysiology observed in infants with severe BPD, and we have previously reported decreased pulmonary miR-29b expression in this model. The current studies tested the hypothesis that adeno-associated 9 (AAV9)-mediated restoration of miR-29b in the developing lung will improve lung alveolarization and minimize the deleterious changes in matrix deposition. Pregnant C3H/HeN mice received an intraperitoneal LPS injection on embryonic day 16 and newborn pups were exposed to 85% oxygen from birth to 14 days of life. On postnatal day 3, AAV9-miR-29b or AAV9-control was administered intranasally. Mouse lung tissues were then analyzed for changes in miR-29 expression, alveolarization, and matrix protein levels and localization. Although only modest improvements in alveolarization were detected in the AAV9-miR29b-treated mice at postnatal day 28, treatment completely attenuated defects in matrix protein expression and localization. Our data suggest that miR-29b restoration may be one component of a novel therapeutic strategy to treat or prevent severe BPD in prematurely born infants.